2024
DOI: 10.1038/s41467-024-46625-w
|View full text |Cite
|
Sign up to set email alerts
|

Shared inflammatory glial cell signature after stab wound injury, revealed by spatial, temporal, and cell-type-specific profiling of the murine cerebral cortex

Christina Koupourtidou,
Veronika Schwarz,
Hananeh Aliee
et al.

Abstract: Traumatic brain injury leads to a highly orchestrated immune- and glial cell response partially responsible for long-lasting disability and the development of secondary neurodegenerative diseases. A holistic understanding of the mechanisms controlling the responses of specific cell types and their crosstalk is required to develop an efficient strategy for better regeneration. Here, we combine spatial and single-cell transcriptomics to chart the transcriptomic signature of the injured male murine cerebral corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…However, not all polarized OPCs migrate, indicating that polarization does not necessarily imply migration. Interestingly, a recent study using a combination of spatial and single-cell RNA transcriptomics identified a subset of OPCs (cluster 15) in the injury core and another group of OPCs (cluster 10) at the periphery ( 39 ). These cluster 15 OPCs may be the polarized cells.…”
Section: Glial Scar Formation and Wound Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, not all polarized OPCs migrate, indicating that polarization does not necessarily imply migration. Interestingly, a recent study using a combination of spatial and single-cell RNA transcriptomics identified a subset of OPCs (cluster 15) in the injury core and another group of OPCs (cluster 10) at the periphery ( 39 ). These cluster 15 OPCs may be the polarized cells.…”
Section: Glial Scar Formation and Wound Healingmentioning
confidence: 99%
“…Interestingly, OPCs also change the expression of TGFβ2 after acute brain injury. Single-cell RNA sequencing of glial cells at the injury site has revealed that both clusters of OPCs (OPC1 and OPC2) upregulate Tgfb2 mRNA ( 39 ). Hence, depleting reactive OPCs at the lesion site may enhance microglial response and inflammation, thereby impeding wound healing.…”
Section: Glial Scar Formation and Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation